PANDANGAN METODOLOGI SADDU AL–DARI’AH TERHADAP PENCOCOKAN NAMA CALON PASANGAN SUAMI ISTRI MENGGUNAKAN HITUNGAN ABAJADUN (Studi Kasus Di Desa Cukir Kecamatan Diwek Kabupaten jombang) - Khoiron Maulana; Abdullah Afif (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Abajadun calculation is a tradition in Indonesian society, particularly in Java, used to match couples and improve relationships within a household. This tradition, originating from the teachings of scholars, reflects the community's strong belief in the significance of name calculations to determine the compatibility of a couple. In this study, the Abajadun calculation is viewed from the perspective of saddu al-dari'ah. The issue raised is how the Abajadun calculation affects the relationship between husband and wife, especially in the context of divorce risks for couples who do not follow it. To answer this question, the researcher uses interview methods with married couples who have experienced problems in their relationships, as well as observation and documentation in Cukir Village, Diwek Subdistrict, Jombang Regency, to collect relevant data regarding the practices and beliefs of the community regarding this calculation.The Abajadun calculation plays a crucial role in determining the success of a relationship. Thus, it provides insight into how the Abajadun calculation functions not only as a tool to match couples but also, according to the principles of saddu al-dari'ah, the objective of every action must be considered. In this case, the goal of the Abajadun calculation is to create a harmonious relationship and prevent potential harm that may arise from the incompatibility of the couple.